Hubungan Aktivitas Fisik, Pola Makan, Konsumsi Fast Food Dan Genetik Dengan Kejadian Obesitas Pada Remaja Di SMKN 2 Banjarbaru Tahun 2016 - Akhmad Mahyuni; Dianita Anggraini; Ema Iriani (HB PRESS, 2017)
Obesity in adolescents has increased in Indonesia over the past few years, obesity must be addressed early on because of the many health risks that can occur in children or adolescents who are obese. Some factors that can lead to obesity is physical activity, dietary habit, fast food and genetic factor. This study aims to determine the correlation of physical activity, diet, fast food and genetic with obesity in adolescents in SMKN 2 Banjarbaru in 2016. This type of research is analytic surve with cross sectional design. The population in this study were 273 people with a total sample were 86 people with proportional random sampling technique. The results showed that the prevalence of obesity in adolescents in SMKN 2 Banjarbaru to 32,6%, for the adolescent physical activity is known that most of the respondents have an active physical activity. The most respondent have dietary habit and fast food was sufficiently. While genetics factor also influence obesity in adolescents. Conclusion were no correlation between physical activity, dietary habit, fast food and genetic factor with obesity incidence in adolescents at SMKN 2 Banjarbaru. In suggestion according to the results of this study were to reactivate monitoring the nutritional status of students through existing UKS